2004
DOI: 10.1111/j.1399-3011.2003.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

A combined extended and helical backbone for Boc‐(Ala‐Leu‐Ac7c‐)2‐OMe*

Abstract: The structure of the peptide Boc-Ala-Leu-Ac7c-Ala-Leu-Ac7c-OMe (Ac7c,1-aminocycloheptane-1-carboxylic acid) is described in crystals. The presence of two Ac7c residues was expected to stabilize a 3(10)-helical fold. Contrary to expectation the structural analysis revealed an unfolded amino terminus, with Ala(1) adopting an extended beta-conformation (Phi=-93 degrees, psi=112 degrees). Residues 2-5 form a 3(10)-helix, stabilized by three successive intramolecular hydrogen bonds. Notably, two NH groups Ala(1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In this section, we show how the concept of kernels allows for accurate calculation of peptide energy. All of their crystal structures are known 9–19 and have been used in the energy calculations presented here. Table II illustrates a variety of natural and synthetic peptides which vary in size, shape, and function.…”
Section: Application Of Kernels To Calculation Of Molecular Energy Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we show how the concept of kernels allows for accurate calculation of peptide energy. All of their crystal structures are known 9–19 and have been used in the energy calculations presented here. Table II illustrates a variety of natural and synthetic peptides which vary in size, shape, and function.…”
Section: Application Of Kernels To Calculation Of Molecular Energy Ofmentioning
confidence: 99%
“…ISARAM and ISARIAX 13 are cyclic rings, containing several unusual amino acid residues and displaying both strong and weak intermolecular H‐bonds. ALAC7 14 is a peptide characterized by packing of cycloheptane rings that stack against one another within the molecule and, throughout its crystal structure in columns. BHLV8 15 incorporates β‐hairpins generated from hybrid peptide sequences containing both α and β amino acids.…”
Section: Application Of Kernels To Calculation Of Molecular Energy Ofmentioning
confidence: 99%
“…Interestingly, even if the saturated cycloheptane ring of Ac 7 c is more flexible than the binaphthyl‐fused ring of Bin, and in 9 out of the 24 crystallographically documented Ac 7 c occurrences in N‐acylated derivatives and peptides one or more ring atoms are disordered over two positions, we found an intriguing relationship between backbone helical screw‐sense and side‐chain torsion angles. Specifically, in the absence of ring disorder, in 9 out of 10 examples of the right‐handed helical Ac 7 c residues, the χ 1,1 torsion angle involving the pro ‐( S ) C γ atom is trans , while χ 1,2 is g + with values comprised between +74° and +93°.…”
Section: Axial Chiralitymentioning
confidence: 73%
“…Tetrasubstitution at the C α atom (C α,α ‐dialkylated amino acids) has been shown to reduce the inherent flexibility of peptide chains , thus facilitating the process of crystallization. Incorporation of C α,α ‐dialkylated amino acids such as α‐aminoisobutyric acid and its analogues in polypeptide sequences has enabled the structural characterization of major secondary structural elements of proteins in medium sized peptides and has provided information which are useful in designing higher levels of protein structures . Extensive studies on C α,α ‐dialkylated amino acid residues with both linear and cycloalkyl side chains have revealed that they favor helical or β‐turn conformations .…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of C α,α ‐dialkylated amino acids such as α‐aminoisobutyric acid and its analogues in polypeptide sequences has enabled the structural characterization of major secondary structural elements of proteins in medium sized peptides and has provided information which are useful in designing higher levels of protein structures . Extensive studies on C α,α ‐dialkylated amino acid residues with both linear and cycloalkyl side chains have revealed that they favor helical or β‐turn conformations . 1‐Amino‐cycloalkane‐1‐carboxylic acid, Ac n c, (where n is the number of atoms in the cycloalkane side chain) with ring sizes (n) varying from 3 to 12 had been incorporated in synthetic peptides and been structurally characterized .…”
Section: Introductionmentioning
confidence: 99%